2014
DOI: 10.1007/s11192-014-1406-4
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric study of China’s science and technology policies: 1949–2010

Abstract: This paper uses a bibliometric analysis method to probe into the evolution of China's science and technology policies from 1949 to 2010, and the roles of core government agencies in policy-making. We obtained 4,707 Chinese S&T policies from GDIS, a Chinese public policy database provided by Tsinghua University. Co-word analysis and network analysis were applied in mapping the topics of S&T policies and collaboration among the agencies, while citation analysis was applied to assess the influence of S&T policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 23 publications
0
50
0
1
Order By: Relevance
“…Co-word analysis identifies relationships between keywords by recording their co-occurrence in policy documents [48]. It is a technique of content analysis for analyzing the strength of association between themes and ideas in textual data [49].…”
Section: Methodsmentioning
confidence: 99%
“…Co-word analysis identifies relationships between keywords by recording their co-occurrence in policy documents [48]. It is a technique of content analysis for analyzing the strength of association between themes and ideas in textual data [49].…”
Section: Methodsmentioning
confidence: 99%
“…Co-word analysis and cluster analysiscommonly used in mapping research topics or tracing patterns (Callon et al 1991;Courtial 1994;Coulter et al 1998;Ding et al 2001;Huang et al 2015)-were employed in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Within the network, the lines connecting different government departments indicate previous cases of joint issuance of documents. The larger the size of a node, the more cases of previous joint issuance there have been (Bonsignore et al 2009;Mohammad et al 2009;De Liddo et al 2011;Hansen et al 2011), which highlights the significant role of that particular policy-making department in that field 6 (Huang et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Fu et al (2015) analyzed malaria research in China and found that Chinese studies on malaria mainly focus on the epidemiology and biomedical fields. Huang et al (2015) used bibliometric analysis to probe into the evolution of China's science and technology policies and the roles of core government agencies in policy-making. analyzed microcystins research in China and worldwide.…”
Section: Literature Reviewmentioning
confidence: 99%